THE RISK FACTOR ANALYSIS OF UPPER ACUTE RESPIRATORY INFECTION IN TODDLERS - Rafifah, Firyal Najla; Fauziah, Henny; Tihardimanto, Andi (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
According to 2016 data from the World Health Organization (WHO), 5.6 million children perished, with acute respiratory infections (ARI) accounting for 16% of these fatalities. As of now, the incidence of Acute Respiratory Infections (ARI) in Indonesia is at 93,260 cases, whereas the global mortality rate attributable to ARI in 2018 was 896,000 children under five years old. The study aimed to identify the risk factors for upper acute respiratory infections in toddlers at Ananda Makassar Hospital and to ascertain the most predominant risk variables for such infections. This research employs an observational analytic methodology utilizing a case-control approach. The purposive sampling technique involved 292 samples, comprising 146 case samples and 146 control samples, derived from medical record data. The results indicated that the Chi-Square derived p-value for age was 0.034 (p<0.05), for gender was 0.16 (p>0.05), for nutritional status was 0.01 (p<0.05), for exclusive breastfeeding history was 0.000 (p<0.05), and for birth weight was 0.094 (p>0.05). Additionally, the multiple regression analysis yielded an odds ratio of 0.641 for the nutritional status variable. This study concludes that a strong link exists between age, nutritional status, and exclusive breastfeeding history with the prevalence of ARI at Ananda Hospital Makassar, where the predominant risk factor for ARI is the nutritional state of toddlers.